Medidas de protección en contravenciones de violencia contra la mujer y miembros del núcleo familiar: casos CJGUNO. - Bonilla, Priscila N. (2023)
This research work focuses on analyzing state protection in cases of violations of violence against women and members of the family nucleus through protection measures issued for the victims. The main objective is to examine whether these measures should be maintained even when a judge issues a sentence of innocence in favor of an alleged aggressor. The study also focuses on the criteria for applying protection measures in cases of domestic violence at the national level, and how the Free Legal Clinic of the University of Otavalo manages to maintain protection measures for victims despite ratifying sentences of innocence. The first chapter addresses the background of the protection measures, as well as the related theoretical and legal foundations present in national and international doctrine and jurisprudence. The second chapter focuses on the criminal process in cases of violence against women and members of the family nucleus, highlighting the importance of protection measures and immediate protection administrative measures (MAPIS).